Performance of Gout Impact Scale in a longitudinal observational study of patients with gout - Wallace, Beth (Rheumatology (Oxford), 2016)
Objective. The aim was to evaluate the reliability, validity and responsiveness to change of the Gout Impact Scale (GIS), a disease-specific measure of patient-reported outcomes, in a multicentre longitudinal prospective cohort of gout patients. Methods. Subjects completed the GIS, a 24-item instrument with five scales: Concern Overall, Medication Side Effects, Unmet Treatment Need, Well-Being during Attack, and Concern Over Attack. The total GIS score was calculated by averaging the GIS scale scores. HAQ-Disability Index (HAQ-DI), Short Form (SF)-36 physical and mental component summaries (PCS and MCS) and physician and patient gout severity assessments were also completed. Reliability was assessed with Cronbach’s α. Baseline GIS scores were compared in subjects with and without gout attacks in the past 3 months using Wilcoxon rank sum tests. Multivariate linear regression was used to evaluate predictors of total GIS. Pearson’s correlation coefficients 0.24–0.36 were considered moderate and >0.37 considered large. The effect size for responsiveness to change was interpreted as follows: 0.20–0.49 small, 0.50–0.79 medium and >0.79 large. Results. In 147 subjects, reliability was acceptable for total GIS (0.93) and all GIS scales (0.82–0.94) except Medication Side Effects and Unmet Treatment Need. Total GIS and all scales except Medication Side Effects discriminated between subjects with and without recent gout attacks (P < 0.05). Total GIS showed moderate-to-large correlations with HAQ-DI, SF-36 PCS and MCS (0.33–0.46). Improvement in total GIS tracked with improved physician and patient severity scores. Worsening physician severity score and recent gout attack predicted worsening total GIS. Conclusion. Total GIS score is reliable, valid and responsive to change in patients with gout, and differentiates between subjects with and without recent gout attacks.